2019
DOI: 10.1021/acsomega.9b01033
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Analysis of Antimicrobial Peptides in Diverse Species

Abstract: This study describes a technical platform that allows us to measure the pore-forming activity of antimicrobial peptides (AMPs) in the lipid bilayer and estimate antimicrobial activity. We selected six different AMPs of diverse species from urochordata to vertebrata and measured the channel current signals using a microfabricated lipid bilayer system. As a result of the electrophysiological measurements, we were able to estimate the pore-forming activity and roughly predict the antimicrobial activity although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…The representative observations of electrophysiological measurements are shown in Figure 3 c. Briefly, cell penetrating peptides (CPPs) exhibit step-like signals [ 16 ]. In contrast, the toroidal pore model exhibits multilevel current signals [ 17 , 18 ]. Based on this knowledge, we performed electrophysiological measurement against 1,2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE)/1,2-dioleoyl- sn -glycero-3-phospho-(1′- rac -glycerol) (DOPG) and 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) bilayer membranes, which mimic the microbial and mammalian cell membranes, respectively, to investigate the action mechanisms on the antimicrobial and hemolytic activities of peptides 1 , 2 , and 8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The representative observations of electrophysiological measurements are shown in Figure 3 c. Briefly, cell penetrating peptides (CPPs) exhibit step-like signals [ 16 ]. In contrast, the toroidal pore model exhibits multilevel current signals [ 17 , 18 ]. Based on this knowledge, we performed electrophysiological measurement against 1,2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE)/1,2-dioleoyl- sn -glycero-3-phospho-(1′- rac -glycerol) (DOPG) and 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) bilayer membranes, which mimic the microbial and mammalian cell membranes, respectively, to investigate the action mechanisms on the antimicrobial and hemolytic activities of peptides 1 , 2 , and 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, treatment of peptide 8 showed a subsequent increase in current signals, which indicates that this peptide could form a pore in the DOPC membrane. It has been reported that the antimicrobial activities of AMPs are positively correlated with the scores for each pore-forming parameter, including pore stability, pore diameter, charge flux, and pore-forming activity [ 18 ]. Each parameter was evaluated as previously reported [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously proposed current signal classification for several different signal shapes, and assigned these to various pore-forming models of α-helical peptides. [50][51][52] In this study, we also classified these signals into four types of current signals: step, square-top, multi-level, and erratic. The definition of signal classification is described in Fig.…”
Section: Confirmation Of Pore Formation Using Channel Current Measurementioning
confidence: 99%
“…We have previously proposed current signal classification for several different signal shapes, and assigned these to various pore-forming models of α-helical peptides. 50,51,52 In this study, we also classified these signals into four types of current signals: step, square-top ( Fig. 3c), multi-level, and erratic (Fig.…”
Section: Confirmation Of Pore Formation Using Channel Current Measurementioning
confidence: 99%